2002
DOI: 10.1128/aem.68.8.3724-3730.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression of the Haloalkane Dehalogenase GenedhmAfromMycobacterium aviumN85 and Preliminary Characterization of DhmA

Abstract: Haloalkane dehalogenases are microbial enzymes that catalyze cleavage of the carbon-halogen bond by a hydrolytic mechanism. Until recently, these enzymes have been isolated only from bacteria living in contaminated environments. In this report we describe cloning of the dehalogenase gene dhmA from Mycobacterium avium subsp. avium N85 isolated from swine mesenteric lymph nodes. The dhmA gene has a G؉C content of 68.21% and codes for a polypeptide that is 301 amino acids long and has a calculated molecular mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 41 publications
(39 reference statements)
2
29
0
Order By: Relevance
“…This property is unique and has not been observed for any other HLD so far. The highest activities of other related enzymes lay in the temperature interval between 40 and 50°C (15,(18)(19)(20)(21)26). Another important finding is that the DpcA enzyme retained almost 27% of its maximal activity at 5°C.…”
mentioning
confidence: 80%
“…This property is unique and has not been observed for any other HLD so far. The highest activities of other related enzymes lay in the temperature interval between 40 and 50°C (15,(18)(19)(20)(21)26). Another important finding is that the DpcA enzyme retained almost 27% of its maximal activity at 5°C.…”
mentioning
confidence: 80%
“…It was recently demonstrated that Mycobacterium tuberculosis H37Rv, the complete genome of which has been sequenced (7), possesses chromosomal genes encoding putative haloalkane dehalogenases (11). Hydrolytic dehalogenation was detected in a number of different mycobacteria (18), and haloalkane dehalogenase DhmA from M. avium N85 has been partially characterized (19). Furthermore, we could find dehalogenase-like open reading frames (ORFs) on the genomes of more than 20 bacterial species.…”
mentioning
confidence: 84%
“…The dehalogenase activity of the purified His-tagged DbjA protein in the presence of 18 halogenated compounds was measured spectrophotometrically ( Table 2). The relative activity data measured for DbjA with 18 different halogenated substrates were complemented with the data collected for other enzymes from the literature, i.e., DhlA (12), DhaA (12), LinB (12), and DhmA (19), and also with the data obtained using a crude extract of E. coli expressing the Trx-DmlA fusion protein FIG. 3.…”
Section: Vol 71 2005 Dehalogenases From Rhizobial Strains 4375mentioning
confidence: 99%
“…[17][18][19] This substrate specificity profile is characteristic of substrate specificity group (SSG)-IV; by contrast, DhlA is categorized in SSG-I. Both DmbB from Mycobacterium bovis 18 and DhmA from Mycobacterium avium N85 21 were categorized in the HLD-I subfamily but their substrate specificities were not reported due to expression and stability problems. The substrate specificity and activity of HLDs have been rationalized by comparing structural differences in the tunnel(s) that provide access to the active site from the surface of the enzyme.…”
Section: Introductionmentioning
confidence: 99%